INFLUENCE OF CLASSROOM CLIMATE ON LEARNING DIFFICULTIES IN MATHEMATICS AMONG SECONDARY SCHOOL STUDENT - B.Janakiraman,; S. Leo Stanly (International Journal of Psychosocial Rehabilitation, 2020)
The present Study is an attempt to find out the Influence of Classroom Climate on Learning Difficulties in Mathematics among Secondary school Students. Classroom Climate scale developed by Shefari Pandiya and Classroom Climate scale containing 35 items and Learning difficulties in mathematics scale developed and standardized by Janakiraman and Dr Leo Stanly and containing 60 items was used to collect the required data. Students studying in standard IX in high and higher secondary schools of Kancheepuram district formed the population. Among these, ten schools were randomly selected .From these three schools, 300 students were selected using lottery method and they were administered the Classroom Climate scale and Learning difficulties in Mathematics scale. The minimum score of the Classroom Climate scale is 35 and maximum score is 140 and learning difficulties in Mathematics scale minimum score is 60 and maximum score is 300 .The findings revealed that there is no significant difference in the classroom climate and learning difficulties in Mathematics of secondary school students with respect to Gender, there is significant difference in classroom climate and learning difficulties in Mathematics of secondary school students with respect to Nature of school and there is significant positive relationship between the classroom climate secondary school students and their learning difficulties in Mathematics.